Analisis Kesalahan Pelafalan Huruf Hijaiyah ’Ro’ Menjadi ’Ra’ Pada Anak-Anak Di Tpq Dusun 1 Desa Talang Alai - Candra, Pasmah; Ernita, Desi; Oktri Hardi, Yola; William Palisu, Toni; Nur Fathonah, Devi; Desasty, Keryns; Julianto, Yolan; Lestari, Mopi; Yolanda, Tri; Evi Hidayah, Rahmi; Putri Utami, Indah (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This study focuses on analyzing the mispronunciation of the Hijaiyah letter ’Ro’ as ’Ra’ among children at TPQ Dusun 1, Desa Talang Alai. Although Arabic is the primary language in Qur’an education, the mispronunciation of Hijaiyah letters, particularly ’Ro’ often pronounced as ’Ra’, affects tajwid understanding and the quality of recitation. This research employs a qualitative method involving observation, interviews, and data analysis. Observational results indicate that mispronunciations are caused by a lack of tajwid understanding, local dialect influence, and inconsistent teaching methods. Strategic recommendations include teacher training, the use of visual and audio media, and regular practice. These findings are expected to enhance the quality of Qur’an education at TPQ Dusun 1 and address the existing pronunciation issues.